Chapter Piattaforme digitali, (big) data, spazio dei flussi/luoghi - Romano, Antonello (Strumenti per la didattica e la ricerca, 2022)
The chapter introduces the Digital Platforms as well as the relationship between platforms - data - space of flows - space of places.